Gibrat's law and the British Industrial Revolution - Alexander Klein; Tim Leunig (University of Kent, School of Economics, 2013)
This paper examines Gibrats law in England and Wales between 1801 and 1911 using a unique data set covering the entire settlement size distribution. We find that Gibrats law broadly holds even in the face of population doubling every fifty years, an industrial and transport trevolution, and the absence of zoning laws to constrain growth. The result is strongest for the later period, and in counties most affected by the industrial revolution. The exception were villages in areas bypassed by the industrial revolution. We argue that agglomeration externalities balanced urban disamenities such as commuting costs and poor living conditions to ensure steady growth of many places, rather than exceptional growth of few.
Keywords: N93; R12; 330; Gibrats law; city-size distribution; industrial revolution